Association between accounting knowledge, AIS utilization and system quality with business performance - Mahadianto, Moh Yudi; Setiawan, Doddy; Hartoko, Sri; Widagdo, Ari Kuncara (International Journal of Innovative Research and Scientific Studies, 2025)
The problem of Small and Medium-Sized Enterprise (SME) business performance (BP) is related to the Accounting Information System Quality (AISQ) concept. Therefore, this study aims to analyze the determinant factors of BP from the AISQ concept in SMEs. Considering the ABC theory-based AISQ framework, several variables complement the model, namely Antecedents (Knowledge of Accounting (KoA) and Accounting Information System Application (AISA)), Behaviors (Accounting Information System (AIS)), and Consequences (BP). The method used is quantitative, with the unit of analysis being SMEs in Cirebon City. This study is based on survey methods using (1) descriptive analysis in measuring responsiveness as well as respondents’ perceptions and causal behaviors, and (2) quantitative analysis. The results show that KoA does not significantly influence BP. However, AISA and AISQ significantly influence the extent of SME BP. These variables affect the ability of SMEs to provide the necessary information to achieve the expected performance.